(3NdGUI GdCHMGK aj TQM fgL GdbQGAGJ GdKdGKs - (3EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdQHYj GdNdjdj HQgGf GdOjf CHhESMGb GdeYQha HGdLYHQjs; (3GdLYHQj , EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd, CHh GSMGb,J (B732 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf cJGH fgL GdOeGKI aj bQGAGJ GdKdGKI eHJcQkG aj Ydeg eNJQYoG aj fXeg de jNd ef MUhd CTcGd s
(3BNQgG (B:s
(3hgeG MGdGf Ch JejjRGf Ci jahM WjHgG bGd GdoeUfa QMeg Gddg JYGdi hgPG BNQ eG jSQ Gddg JYGdi ef EedGA TQM GdfgL s
(3Vef eLehY , JQJjHgG (B: (3ef U (B168 - (3U(B218s
(3GdfSNI HgG MhGTs
(3Ydjg eWGdYI HGdhQbI GdCNjQI ef GdeNWhW HGSe eMeO Hf YeQ Hf YKeGf GdMfajs
(3hHgG JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs